EHealth for service delivery in conflict: a narrative review of the application of eHealth technologies in contemporary conflict settings. Issue 6 (16th April 2021) - Bowsher, Gemma; El Achi, Nassim; Augustin, Katrin; Meagher, Kristen; Ekzayez, Abdulkarim; Roberts, Bayard; Patel, Preeti
Abstract: The role of eHealth in conflict settings is increasingly important to address geographic, epidemiologic and clinical disparities. This study categorizes various forms of eHealth usage in conflict and aims to identify gaps in evidence to make recommendations for further research and practice. The analysis was carried out via a narrative hermeneutic review methodology. Articles that fulfilled the following screening criteria were reviewed: (1) describing an eHealth intervention in active conflict or ongoing insurgency, (2) an eHealth intervention targeting a conflict-affected population, (3) an e-learning platform for delivery in conflict settings and (4) non-interventional descriptive reviews relating to eHealth in conflict. Of the 489 papers eligible for screening, 46 merited final inclusion. Conflict settings described include Somalia, Sudan, Afghanistan, Syria, Iraq, Pakistan, Chechnya, Gaza and the Democratic Republic of Congo. Thirty-six studies described specific eHealth initiatives, while the remainder were more generic review papers exploring general principles. Analysis resulted in the elucidation of three final categories of current eHealth activity in conflict-affected settings: (1) eHealth for clinical management, (2) e-learning for healthcare in conflict and (3) eHealth for information management in conflict. Obvious disparities in the distribution of technological dividends from eHealth in conflict are demonstrated by this review. Conflict-affected populations are predominantly subject to ad hoc and voluntary initiatives delivered by diaspora and civil society organizations. While the deployment of eHealth technologies in conflict settings is increasingly normalized, there is a need for further clarification of global norms relating to practice in this context.